Primary cervico‐uterine anastomosis in a patient with agenesis of the uterine isthmus: A case report and review. Issue 12 (9th September 2018) - Richards, Amy; Phy, Jennifer L.; Huang, Jaou‐Chen
Abstract: Arrested caudal extension of the fused Müllerian ducts, either complete or segmental, causes obstruction of the outflow tract. We describe a case of agenesis of the uterine isthmus and the procedure to establish the continuity of the outflow tract. A 15‐year‐old girl with cyclic pelvic pain and amenorrhea was found to have a 3‐cm gap between the uterine body and the cervix. After cervico‐uterine anastomosis via laparotomy she menstruated normally and was pain‐free. Selected cases of arrested Müllerian duct extension can be corrected by primary anastomosis, which establishes anatomical continuity and restores menstruation and, possibly, future fertility.